SORPTION OF AS5+ FROM AQUEOUS SOLUTION BY LEPIDOCROCIT (γ-FEOOH) NANOPARTICLE - Nguyễn, Đình Trung (2022)
Abstractγ-FeOOH nanorods adsorbent for As5+ removal was prepared by a chemical co-precipitation method. The maximum adsorption capacities for As5+was 63.75 mg/g at pH= 6.0, higher than of Fe2O3, Fe3O4... The adsorption data accorded with Freundlich isotherms. At study pH, for arsen, the adsorption equilibrium was gained after 90 min. Kinetic data fitted well to the pseudo-second-order reaction model. Competitive ions hindered the adsorption according to the decreasing sequence sulfate, ammonium and chloride. The high adsorption capability and good performance on other aspects make the γ-FeOOH nanorods a promissing adsorbent for the removal of As (V) from groundwater.Keywords：As ; sorption; kinetic; γ-FeOOH nanoTOM TATγ-FeOOH dang nano dung lam vat lieu hap phu As5+ duoc dieu che bang phuong phap dong ket tua. Tai pH = 6,0, dung luong hap phu cuc dai cua vat lieu doi voi As5+ la 63,75 mg/g, cao hon so voi mot so vat lieu lam chat hap phu asen nhu Fe2O3, Fe3O4. Mo hinh hap phu dang nhiet Freundlich phu hop mo ta qua trinh hap phu As5+ boi γ-FeOOH, thoi gian dat can bang hap phu la 90 phut. Dong hoc hap phu tuan theo phuong trinh dong hoc hap phu bac 2. Xuat hien canh tranh cua cac ion la voi As5+ trong qua trinh hap phu tuan theo trat tu giam dan tu sulfate, amonium va chloride. Dung luong hap phu cuc dai cua vat lieu, cung nhu viec dieu che de dang, gia thanh thap cua γ-FeOOH, lam cho no tro thanh chat hap phu hap dan va day hua hen trong viec xu ly asen trong nuoc ngam.